Chemotaxis and nod Gene Activity of Bradyrhizobium japonicum in Response to Hydroxycinnamic Acids and Isoflavonoids - Kape, Rüdiger (1991)
For Bradyrhizobium japonicum, the chemotactic and the nod gene-inducing effects of hydroxycinnamic acids and two of their derivatives were compared with those of isoflavonoids. Only the hydroxycinnamic acids were strong chemoattractants, while the other substances tested were chemotactically inactive. Besides the known nod gene induction by isoflavonoids, a weak nod gene induction by coniferyl alcohol, chlorogenic acid, and ferulic acid was found.